Effects of tomato juice consumption on plasma and lipoprotein carotenoid concentrations and the susceptibility of low density lipoprotein to oxidative modification - Maruyama, C. (Japan Women's Univ., Tokyo); Imamura, K; Oshima, S; Suzukawa, M; Egami, S; Tonomoto, M; Baba, N; Harada, M; Ayaori, M; Inakuma, T; Ishikawa, T (Journal of Nutritional Science and Vitaminology, 2001)
Effects of tomato juice supplementation on the carotenoid concentration in lipoprotein fractions and the oxidative susceptibility of LDL were investigated in 31 healthy Japanese female students. These subjects were randomized to one of three treatment groups; Control, Low and High. The Control, Low and High groups consumed 480 g of a control drink, 160 g of tomato juice plus 320 g of the control drink, and 480 g of tomato juice, providing 0, 15 and 45 mg of lycopene, respectively, for one menstrual cycle. The ingestion of tomato juice, rich in lycopene but having little beta-carotene, increased both lycopene and beta-carotene. Sixty-nine percent of lycopene in plasma was distributed in the LDL fraction and 24% in the HDL fraction. In the Low group, the lycopene concentration increased 160% each in the VLDL+IDL, LDL and HDL fractions (rho < 0.01). In the High group, the lycopene concentration increased 270% each in the VLDL + IDL and LDL fractions, and 330% in the HDL fraction (rho < 0.01). beta-Carotene also increased 120%, and 180% in LDL fractions of the Low and the High groups, respectively. Despite these carotenoid increases in LDL, the lag time before oxidation was not prolonged as compared with that of the Control group. The propagation rate decreased significantly after consumption In the High group. Multiple regression analysis showed a positive correlation between lag time changes and changes in the alpha-tocopherol concentration per triglyceride in LDL, and a negative correlation between propagation rate changes and changes in the lycopene concentration per phospholipid in LDL. These data suggest that alpha-tocopherol is a major determinant in protecting LDL from oxidation, while lycopene from tomato juice supplementaion may contribute to protect phospholipid in LDL from oxidation. Thus, oral intake of lycopene might be beneficial for ameliorating atherosclerosis.